Answer:
[tex]x=-\frac{3}{2},-1[/tex]
Step-by-step explanation:
[tex]2x^2+5x+3=0[/tex]
Split the second term (5x) into two terms. Multiply the coefficient of the first term (2) by the constant term (3):
[tex]2*3=6[/tex]
Find which two numbers add up to 5 and multiply into 6:
[tex]3+2=5\\3*2=6\\3,2[/tex]
Split 5x as the sum of 3x and 2x:
[tex]2x^2+3x+2x+3[/tex]
Now factor out a common term for the first 2 terms:
[tex]2x^2+3x\\x(2x+3)[/tex]
And do the same for the last 2 terms:
[tex]2x+3\\1(2x+3)[/tex]
Re-insert:
[tex]x(2x+3)+1(2x+3)=0[/tex]
Factor out the common term 2x+3 and insert the values in front of the parentheses (x and 1):
[tex](2x+3)(x+1)=0[/tex]
Separate the parentheses and equal them to 0. Solve for x:
[tex]2x+3=0\\2x+3-3=0-3\\2x=-3\\\\\frac{2x}{2}=\frac{-3}{2}\\\\ x=-\frac{3}{2}[/tex]
and
[tex]x+1=0\\x+1-1=0-1\\x=-1[/tex]